Internet of Things and the network economics of operator platforms - Günter Knieps (International Telecommunications Society (ITS), 2019)
Disruption of tradition network industries and the emergence of innovative physical operator platforms provide challenging governance problems of contractual relationships among different actors involved. The problem solution competence of operator platforms (two-sided, multi-sided) is the entrepreneurial search for the required governance structures. Operator platforms need as input a combination of physical networks and network services with complementary (big data) virtual networks. The problem of division of labor between all-IP broadband network providers, virtual network service providers and platform operators arises concomitant with the implementation of adequate governance structures.
Keywords: L51; L92; L96; O31; 330; Internet of things; operator platforms; governance; sharing economy